Acute myocardial infarction induced by avatrombopag: a case report - Junqi, Gou; Chaohui, Liu; Mingjian, Lang; Fengyou, Yao (Frontiers in Pharmacology, 2025)
BackgroundAvatrombopag, a thrombopoietin receptor agonist (TPO-RA), is used for immune thrombocytopenia (ITP) but confers thrombotic risks. Acute myocardial infarction (AMI) as an adverse event is underreported.SummaryA 58-year-old female with steroid-refractory ITP developed ST-elevation myocardial infarction (STEMI) 5 days after initiating avatrombopag monotherapy (20 mg/day). She had no history of traditional cardiovascular risk factors. Her platelet count increased from two to 122 × 109/L before AMI. Coronary angiography revealed thrombotic occlusion of the left ventricular posterior branch, treated with thrombus aspiration. Dual antiplatelet therapy was initiated, and avatrombopag was discontinued. The patient was discharged on day 10 post-AMI. At the 14-day follow-up, thrombocytopenia recurred (platelets 18 × 109/L), requiring avatrombopag re-initiation alongside aspirin. No further thrombosis occurred.ConclusionAvatrombopag monotherapy may induce rapid coronary thrombosis. Prophylactic antiplatelet therapy and maintaining platelets at 50–150 × 109/L are critical during TPO-RA treatment. This case highlights the need for thrombotic risk assessment before TPO-RA initiation.